STUDENTS’ MATHEMATICAL PROBLEM-SOLVING ABILITIES IN ALGEBRAIC EXPRESSIONS AT SMP NEGERI 48 PALEMBANG - Husen, Sadam; Jumroh (CV. Doki Course and Training, 2025)
This study aims to assess the mathematical problem-solving abilities of students at SMP Negeri 48 Palembang in the topic of algebraic expressions. The research sample was selected randomly, consisting of 25 students. Data collection was conducted using essay-format test questions. The research employed a quantitative descriptive method. Based on data analysis and discussion, it can be concluded that students' mathematical problem-solving abilities are categorized as moderate, with an average score of 67.90. The students' abilities in solving problems based on specific indicators are as follows: understanding the problem (74.33), planning the solution (74.67), executing the plan (65.00), and interpreting the results (59.00).